Angiopoietin-Like Protein 8/Leptin Crosstalk Influences Cardiac Mass in Youths With Cardiometabolic Risk: The BCAMS Study - Wang, Dongmei; Feng, Dan; Wang, Yuhan; Dong, Peiyu; Wang, Yonghui; Zhong, Ling; Li, Bo; Fu, Junling; Xiao, Xinhua; Speakman, John R.; Li, Ming; Gao, Shan (Frontiers in Endocrinology, 2022)
Objectives: The link between excess adiposity and left ventricular hypertrophy is multifaceted with sparse data among youths. Given that adipokines/hepatokines may influence lipid metabolism in myocardium, we aimed to investigate the relation of the novel hepatokine angiopoietin-like protein 8 (ANGPTL8) and other adipokines with cardiac structure in a cohort of youths and explore to what extent these adipokines/hepatokines affect cardiac structure through lipids. Methods: A total of 551 participants (aged 15-28 years) from the Beijing Child and Adolescent Metabolic Syndrome Study (BCAMS) cohort underwent echocardiographic measurements plus a blood draw assayed for five adipokines/hepatokines including adiponectin, leptin, retinol binding protein 4, fibroblast growth protein 21 and ANGPTL8. Results: Both ANGPTL8 (β = -0.68 g/m2.7 per z-score, P= 0.015) and leptin (β = -1.04 g/m2.7 per z-score, P= 0.036) were significantly inversely associated with left ventricular mass index (LVMI) independent of classical risk factors. Total cholesterol and low-density lipoprotein cholesterol significantly mediated the ANGPTL8–LVMI association (proportion: 19.0% and 17.1%, respectively), while the mediation effect of triglyceride on the ANGPTL8–LVMI relationship was strongly moderated by leptin levels, significantly accounting for 20% of the total effect among participants with higher leptin levels. Other adipokines/hepatokines showed no significant association with LVMI after adjustment for body mass index. Conclusions: Our findings suggest ANGPTL8, particularly interacting with leptin, might have a protective role in cardiac remodeling among youths with risk for metabolic syndrome. Our results offer insights into the pathogenesis of the cardiomyopathy and the potential importance of tissue-tissue crosstalk in these effects.